Effect of Traditional Massage Stimulation on Interleukin 6 (IL-6) Serum Level on Stunted Children - Sueca, I Nyoman; Anton, Sri Sulistyawati; Dewi, Ni Made Umi Kartika; Diaris, Ni Made; Warmayana, I Gede Agus Krisna; Sinarsih, Ni Ketut; Armini, Ni Wayan Yusi (AIBPM Publisher, 2024)
Failure to thrive or stunting is a major complication of chronic inflammation and recurrent infections in children. An uncontrolled inflammatory response is associated with stunting syndrome. Mediators that play a role include IL-6. This study aims to determine the effect of traditional massage stimulation on IL-6 serum levels in stunted children aged 12 – 60 months. This study is a quasi-experimental design involving 21 stunted children who received the 15-minute massage treatment three times a week for four weeks. Examination of IL-6 serum levels was carried out using the ELISA method using the Human IL-6 ELISA Kit RAB 0306-1KT Sigma-Aldrich. The serum IL-6 levels before the intervention (60,234pg/ml) had a higher mean value than serum IL-6 after intervention (21,261pg/ml). The paired t-test showed a significant difference in the children's serum IL-6 values before and after the massage intervention (p0.000). It was concluded that traditional massage stimulation reduces Interleukin 6 (IL-6) serum levels in stunted children.